Appearance of a colovesical fistula at cystoscopy. Issue 11 (22nd September 2015) - Aiken, William D.; Reid, Gareth; Powell, Leo‐Paul
Key Clinical Message: Colovesical fistulae typically present with pneumaturia and/or fecaluria. Diverticulitis, inflammatory bowel disease, and malignancies of the colon are the commonest causes. The fistulous tract and adjacent organs are best demonstrated by contrast‐enhanced CT scan with rectal contrast or MRI. Biopsy at cystoscopy/colonoscopy is necessary for complete evaluation and treatment planning. Abstract : Colovesical fistulae typically present with pneumaturia and/or fecaluria. Diverticulitis, inflammatory bowel disease, and malignancies of the colon are the commonest causes. The fistulous tract and adjacent organs are best demonstrated by contrast‐enhanced CT scan with rectal contrast or MRI. Biopsy at cystoscopy/colonoscopy is necessary for complete evaluation and treatment planning.